2012
DOI: 10.1590/s0037-86822012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Leishmania (Leishmania) chagasi infection in dogs and the relationship with environmental and sanitary aspects in the municipality of Palmas, state of Tocantins, Brazil

Abstract: INTRODUCTION: The aim of the present study was to identify the presence of Leishmania (Leishmania) chagasi infection in dogs in the City of Palmas, Tocantins, Brazil, using the PCR technique to list the hot spots of infected dogs in the city and associate their occurrence to significant environmental changes at capture sites. METHODS: DNA was extracted from blood of dogs, and the PCR were performed with primers RV1/RV2. After screening the population studied, the regions of the city that had the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
2
11
0
2
Order By: Relevance
“…and 58% L. infantum) is almost similar to other studies also using peripheral blood, i.e. Bigeli et al (2012) blood. Leishmania parasites have a high number of kDNA minicircles copies (10,000 copies) per parasite, which increases the sensitivity of the assay (Quaresma et al 2009;Solc a et al 2012), as observed in this study with »10 0 parasite mL ¡1 .…”
Section: Discussionsupporting
confidence: 90%
“…and 58% L. infantum) is almost similar to other studies also using peripheral blood, i.e. Bigeli et al (2012) blood. Leishmania parasites have a high number of kDNA minicircles copies (10,000 copies) per parasite, which increases the sensitivity of the assay (Quaresma et al 2009;Solc a et al 2012), as observed in this study with »10 0 parasite mL ¡1 .…”
Section: Discussionsupporting
confidence: 90%
“…Worldwide, and in Brazil, the number of dogs infected with L. infantum varies from 20 to 90% (Coura-Vital et al, 2011;Bigeli et al, 2012); however, in the studied region, there was no record of this parasite affecting humans or animals. There is also no evidence of the presence of Lutzomyia longipalpis in the municipality of Ilhéus (Carvalho et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…The presence of dogs in intradomicile and not in peridomicile was observed during the period of capture. The presence of dogs inside the houses is also considered an important factor, as they can act as a food source for females, serving as potential reservoirs of the disease, according to studies of Bigeli; Oliveira-Júnior; Teles [25]. …”
Section: Discussionmentioning
confidence: 99%